(untitled) (Computer systems and information technologies, 2022)
The problem of fleeting time and its effective use has deep roots in human history. Many generations have asked the question of what time is, how it can be controlled, and if it cannot be controlled, how to deal with this enormous influence on human life. Time is the most valuable resource that you have to learn to manage. The more we manage to do, the better the quality of our work and life in general. And in the conditions of digital transformation and acceleration of changes, a clear order sometimes helps to maintain focus on goals, not to deviate from the course, and, ultimately, to be in demand in the labor market. The main drivers of the time management system are management methods and techniques. Techniques allow different ways to compose a plan for different periods and evaluate priority. The methods, in turn, solve the issue of the implementation of this plan. The implementation tool is no less important, and here information systems have offered themselves very well. The possibility of dynamic planning, scalability, a system of reminders, and a system of rewards - all reflects powerful solutions for the introduction of time management. This work offers an overview of the process of developing a convenient information system with time management methods. A study of time management methods was conducted. An information model was developed that combines Pomodoro techniques, ABC analysis based on the Eisenhower principle, and Getting Things Done. This model allows you to classify tasks according to the degree of importance, divide them into different groups and lists, assign time for long-term and short-term tasks, and analyze the degree of completion of each task and the work as a whole. Modeling of the information system was carried out using the unified modeling language UML and its diagrams of precedents, deployment, classes, packages, and components, which simplify the creation of the application logic and reflect the structure of the application. The design of the system was also carried out using the creation of a prototype in the online vector service Figma. The information system is implemented as a client-server web-oriented application based on the MERN technology stack. React is used to develop the web application interface, Node.js, and the Express.js framework for the application server, which implements the creation and request of APIs for communicating with the document-oriented database management system MongoDB using the mongoose module.